Penerapan Customer Relationship Management (CRM) Pada Pemasaran Sparepart Mobil Dan Motor Pada Toko Fajar 88 Berbasis Web - Marjuni Ribka; Nasrullah, Nasrullah; Fauzi Razak; Wayan Suparno (Ikatan Ahli Informatika Indonesia, 2023)
88 Stores in finding new customers and retaining their customers makes it difficult for their business to develop. The purpose of this research is to help owners improve their business and manage data such as customer data, order data, FeedBack, and stock items as well as help customers find out what products are available at the Fajar 88 store. The research design used is UML (Unified Modeling Language), which is designed in a structured manner consisting of use case diagrams, activity diagrams sequence diagrams and class diagrams. With the method of collecting observational data. The results of this study are the application of Customer Relationship Management (CRM) in Marketing of Car and Motorcycle Spare Parts at the Web Based Fajar 88 Store which can assist customers in accessing information about the products being sold and in placing product orders, as well as on the Fajar 88 store making it easier management of information and marketing data, how to acquire new customers to retain their customers to become loyal customers.